The Intersectional Battlefield: Reimagining Dalit Identity, Resistance, and Agency in the Works of Meena Kandasamy - Kesari Kumari,; Dr Rakesh Kumar, (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Meena Kandasamy’s corpus represents a crucial intersectional feminist intervention in Dalit literature, moving beyond singular narratives of caste oppression to explore the complex duality of marginalized identity.1 This paper analyzes how Kandasamy meticulously dissects the experiences of Dalit men and women across three key thematic fields. First, it examines the Contradictory Politics of Dalit Masculinity, highlighting its simultaneous function as resistance against caste hegemony and a critical site for the reproduction of internal patriarchal structures. Second, it investigates the Poetics of Trauma and Survival, focusing on the revolutionary mechanisms of memory, testimony, and confession used to dismantle enforced silence. Third, it argues that Kandasamy elevates Anger as Radical Political Resistance, transforming a negative emotion into a strategic, unifying, and moral tool for challenging the double hierarchy of caste and gender.2 The study concludes that Kandasamy’s fearless literary activism is a demand for a holistic liberation that requires the simultaneous condemnation and dismantling of the external caste setup and the internalized gender repression, restructuring the understanding of Dalit identity as a project of radical social justice.
Keywords: Meena Kandasamy; Dalit Literature; Intersectionality; Dalit Masculinity; Feminist Resistance; Testimony; Political Anger; Patriarchy; Caste Oppression